To be a professional in the knowledge society - Gadea Rubio, Cecilia (2008)
Nowadays talking on informarion, data and knowledge is a predominant subject leading our professional, social and even emocional acts. That is because our sociery is getting involved into a new age, a new current, a new stage, a new goal which is that of lifelong learning and immersion in knowledge. T he current professional, facing the age of transformarion and globalization, is invited to participare in this sociery, so that his participation instead an invitation beco me a demand or duty to be immediately answered under derriment ro remain only as spectaror and ro feel untied in a future from this demanding social link in the age of knowledge. Questions such as: How ro participare in this society? How ro joint it permantely? or Which is the role played by the current professional?What changes are manifested during this development due ro the use ofTIC'S? are sorne of the reflections this paper brings to the reader for his/her own growing and identification as an individual and a part of knowledge.